Larvicidal Activity of Brugmansia candida against Aedes aegypti and Culex quinquefasciatus (Diptera: Culicidae) - Setiawan Khoirul Himmi; Didi Tarmadi; Dita Meisyara; Anugerah Fajar; Titik Kartika; Ikhsan Guswenrivo; Sulaeman Yusuf (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Mosquitoes are well known as vectors of hazardous diseases for human. Plant extracts can be used as an alternative for larval control due to they are a rich source of bioactive chemicals and safe for the environment. The present study investigated the larvicidal activity of crude extracts derived from leaf and flower of Brugmansia candida against the second larval instar of Aedes aegypti and Culex quinquefasciatus. The larval mortality was observed at 24 and 48 h exposure of both leaf and flower extracts, at the concentration of 100, 250, 500, and 1000 ppm. The 24 h exposure of both extracts at the concentration of 500 and 1000 ppm resulted in larval mortality rates were significantly lower than those of 48 h exposure. However, the mortality rate was not significantly different at the lower concentrations of crude extracts. The results also suggested that there was no significant difference in the larvicidal effect between leaf and flower extracts at 24 and 48 h exposure for all concentrations. The LC50 values at 48 h exposure for leaf extract were 789 and 791 ppm for Ae. aegypti and C. quinquefasciatus, respectively, whereas for flower extract were 772 and 780 ppm for Ae. aegypti and C. quinquefasciatus, respectively. Overall, B. candida showed larvicidal activity against Ae. aegypti and C. quinquefasciatus. This research contributes to new finding regarding the larvicidal activity of B. candida. This finding also supports the next study to develop B. candida as an alternative source for larval control agent.